2017
DOI: 10.1186/s12933-017-0534-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel diameters and reactivity in diabetes mellitus and/or cardiovascular disease

Abstract: BackgroundRetinal vessel calibre and vascular dilation/constriction in response to flicker light provocation may provide a measure distinguishing patients suffering from diabetes mellitus and/or cardiovascular disease.MethodsOne hundred and sixteen age and sex matched patients with diabetes mellitus (DM), cardiovascular disease (CVD) and both DM and CVD (DM + CVD) underwent systemic and intraocular pressure measurements. Retinal vessel calibres were assessed using a validated computer-based program to compute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
(48 reference statements)
2
16
0
Order By: Relevance
“…It is therefore possible that the high proportion of patients with increased levels of systemic inflammation in this study might attenuate the association between retinal venular diameter and DM. This is confirmed by the study of Heitmar et al, in which no association was found between retinal vessel diameter and DM in different patients groups with increased levels of inflammation 42 .…”
Section: Discussionsupporting
confidence: 64%
“…It is therefore possible that the high proportion of patients with increased levels of systemic inflammation in this study might attenuate the association between retinal venular diameter and DM. This is confirmed by the study of Heitmar et al, in which no association was found between retinal vessel diameter and DM in different patients groups with increased levels of inflammation 42 .…”
Section: Discussionsupporting
confidence: 64%
“…Cardiovascular risk factors like diabetes mellitus have been shown to alter retinal vessel diameters and/or responses to stimulation ( 32 ) and could thus act as important confounding factors. There was only one patient with diabetes in our study, excluding further analysis of its potential as a confounding factor.…”
Section: Resultsmentioning
confidence: 99%
“… 5 6 Specifically, vessel calibre measurements have been correlated with worsening of eye diseases such as diabetic retinopathy 7 and systemic health status in hypertension, 8 diabetic nephropathy 9 and cardiovascular disease. 10 Therefore, accurate and reliable measurements of the retinal vessel calibre with OCTA may be attractive. Recently, Ghasemi Falavarjani et al 11 compared the vessel diameter measurements obtained from OCTA scans and fundus photographs, and reported that the vessels measured from OCTA scans appeared to be nearly 20 µm thicker when compared with fundus photographs.…”
Section: Introductionmentioning
confidence: 99%